Performance Optimization based Spectrum Analysis on OFRA and EDFA Devices - Liu Liying; Ma Yu; Yang Jiuru (Institute of Advanced Engineering and Science, 2013)
As the key devices, erbium doped fiber amplifier (EDFA) and optical Raman fiber amplifier (OFRA) have been widely applied in the fields of optical communication, sensing and measurement. However, the performance optimization is always one of the hot topics in the study of optical fiber amplifiers, because its output characteristics are hardly dependent to the key designing parameters. In this paper, in order to cope with such problem, we adopt the novel analysis based spectrum to study the output performance of EDFA and OFRA systems, respectively. Through simulating the operation of the two amplifying system, their output characteristics are first demonstrated with the various parameters. And according to the numerical results obtained, the key designing parameters of EDFA and OFRA systems are determinate, and the performance of amplifying systems are improved and optimized obviously in terms of output power, signal noise ratio, and the level of gain flatness. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2822 Keywords: Fiber Raman Amplifier, Erbium Doped Fiber Amplifier, Performance optimization, Spectrum analysis, Simulation.